Abridge Classis : Treasure island (Kiddo, 2020)
Join Jim Hawkins as he embarks on the adventure of a lifetime to the treacherous Treasure Island-a voyage filled with swashbuckling pirates, dastardly schemes, and unforgettable characters such as Long John Silver. This action-packed tale has been retold and adapted with new illustrations, making it perfect for younger readers.